A rural tourism promotion mechanism based on virtual reality technology for real-time interactive experience - Bo Han; Jia Yu; Mingyan Bi (Systems and Soft Computing)
With the development of the social economy, rural tourism has increasingly attracted global attention due to its important role in promoting local economic revitalization and cultural preservation. However, traditional rural tourism promotion methods suffer from low information transmission efficiency, shallow user experience, and insufficient interactivity, severely restricting the attractiveness and development potential of rural tourism. To address these issues, this study proposes a real-time interactive tourism promotion method based on virtual reality technology, aiming to enhance user experience, immersion, and participation. The method involves collecting environmental data from rural areas, constructing realistic three-dimensional scenes, and integrating a multi-touch interaction system. A series of experiments were conducted to evaluate the system's effectiveness before and after optimization. The results showed an enhancement in system stability, with an increase from 0.62 to 0.86, an improvement in accuracy to 0.81, and a notable increase in response rate from 0.13 to 0.76. Compared with existing online recommendation systems, the method achieved higher accuracy at 92.27 %, recall at 82.21 %, and F1-score at 84.51 %. In terms of user behavior, behavioral intention increased from 8.16 to 98.57, immersion rose from 13.08 to 93.24, and operability improved from 6.37 to 88.75. In three pilot villages, tourism awareness and booking rates increased by over 12 % and 15 %, respectively. Economic performance also showed notable improvement, with the cost-effectiveness ratio reaching 98.37 and revenue growth reaching 97.88. The results demonstrate that the real-time interactive promotion mechanism based on VR technology can effectively enhance the communication, user conversion rate, and economic benefits of rural tourism, providing new technical support and practical pathways for rural revitalization and sustainable development.